2014
DOI: 10.1108/ijhcqa-01-2014-0013
|View full text |Cite
|
Sign up to set email alerts
|

Are adequate fluid challenges prescribed for severe sepsis?

Abstract: This, the first case-based survey the authors could find, highlights an issue requiring significant improvement. The implications are likely to be relevant to clinicians in all UK hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…It was uncommon, however, to take the patient’s body weight into account [ 37 , 45 ]. A questionnaire survey using case vignettes showed that, contrary to current guidance for IV fluid resuscitation in sepsis [ 46 ], junior doctors’ choices of IV fluid volumes were unrelated to body weight. In some instances, junior doctors were unaware of available guidance or struggled to reconcile differences between directives [ 2 , 29 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was uncommon, however, to take the patient’s body weight into account [ 37 , 45 ]. A questionnaire survey using case vignettes showed that, contrary to current guidance for IV fluid resuscitation in sepsis [ 46 ], junior doctors’ choices of IV fluid volumes were unrelated to body weight. In some instances, junior doctors were unaware of available guidance or struggled to reconcile differences between directives [ 2 , 29 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Responses were compared with the Surviving Sepsis Campaign's recommended volume during the study (20 ml/kg). [9]. This similarity in poor management results only shows that its due to poor training and focus upon sepsis as a topic regarding its management.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Matthew Toward, Rajesh Jain, Milind Rao done in in two UK hospitals, with 77 questionnaires were completed. In 2014 that showed there was no signi cant difference between doctor grades (FY1 and SHO) in any scenario[9]. This is most likely that Sepsis as topic overall is complicated when it comes to de nition and perception of its diagnostic criteria, and poor training might have a signi cant role in it as well.…”
mentioning
confidence: 97%
“…An optimization-driven tool could support junior doctors in determining optimal IV fluid treatments, who are usually among the first to treat patients. Courtney et al (2014) studied the infusion of intravenous fluids to patients by junior doctors. The study found that the majority of junior doctors do not prescribe the right amount of fluid and fail to adjust for volume by mass [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…SSC guidelines recommend varying the amount of fluid infusion at different disease severity levels. The study showed that 20% of all adults receiving fluid resuscitation experience complications owing to inadequate quantity of fluid resuscitation [6]. By the time senior doctors review the treatment, the early intervention window has passed, which is critical for sepsis treatment [7].…”
Section: Introductionmentioning
confidence: 99%